The Effect of Management Knowledge Influences the Preparation of MSMEs Financial Statements - Hikmahwati; Rusman Irwansyah (Ilomata International Journal of Tax and Accounting, 2023)
The rapid development of the MSME sector shows that there is great potential if this can be managed and developed well which will certainly be able to create strong micro, small and medium enterprises. The main problem in developing MSMEs is related to presenting financial reports. The inability to present quality financial reports is one of the weaknesses of management. This condition also occurs among MSME business actors in Banjarmasin. This has an impact on the difficulty of MSME actors in evaluating their operational performance. There is still not much research related to management knowledge in preparing financial reports for MSME players. So the aim of this research is to analyze how management knowledge influences the preparation of MSME financial reports in Banjarmasin City. The population of this research is MSMEs registered with the Banjarmasin City Cooperative and Industrial Service. Takes the form of a descriptive quantitative approach. The method used is Linear Regression, namely testing the Goodness and Fit Model, the feasibility of this model can be seen in the determination test (R-Square) and F Test. The results of the hypothesis test state that management knowledge influences the preparation of MSME financial reports in Banjarmasin City with a significance value (Sig ) is 0.000. The influence of management knowledge on the preparation of financial reports is 45.7%.